PENDIDIKAN KARAKTER AGAMA DALAM PEMBELAJARAN SENI: RELIGIOUS CHARACTER EDUCATION IN ART LEARNING - Dwina Mada Kamila; Agus Cahyono; Muh. Fakhrihun Naam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Islamic character values that include piety, honesty, discipline, tolerance, and social concern must be internalized from an early age. To address the challenges of internalization that tend to be rigid, approaches through art, particularly visual expression, become relevant. Visual arts, like drawing, are the universal language of children that facilitate authentic self-expression, where emotions, understanding, and values can be realized without verbal barriers, thus becoming a potential medium for instilling character. This research uses a qualitative approach with literature review or by looking at previous research as reference material in article writing. Based on the results of the research obtained, children's drawings can be a very effective foundation for knowing character education in children. In addition, it helps shape children into better individuals, have strong characters, balance emotionally, intellectually, socially, and spiritually. Integrative in character education through religion and art provides significant theoretical benefits in synthesizing the philosophy of Islamic education, fine arts education, and the psychology of child development.